Development and Performance Evaluation of a GRBL-Based CNC Router for Non-Metallic Material Engraving - Rouhillah; Inzar Salfikar; M. Rifaldi (Politeknik Aceh, 2026)
This study aims to design, develop, and evaluate the performance of a GRBL-based Computer Numerical Control (CNC) router for contour engraving on non-metallic materials, such as acrylic and wood. The research methodology consisted of mechanical system design, component fabrication through milling and drilling processes, mechanical and electronic assembly, GRBL firmware integration, and machine accuracy testing. Standard commercially available components were utilized to simplify the manufacturing and maintenance processes. Performance evaluation was conducted by comparing the machined dimensions with the programmed design generated using G-code. The experimental results demonstrated that the developed CNC router was capable of producing contour engravings consistent with the intended along the X-, Y-, and Z-axes. These findings indicate that the proposed system provides satisfactory accuracy for light machining and engraving applications on non-metallic materials. Therefore, the developed CNC router offers a cost-effective and reliable solution for educational activities, research, and prototype manufacturing in laboratory environments.